Teaching from the primary inorganic literature: lessons from Richard Andersen. Issue 39 (20th September 2018) - Stewart, Joanne L.; Bentley, Anne K.; Johnson, Adam R.; Nataro, Chip; Reisner, Barbara A.; Watson, Lori A.
Abstract : Teaching inorganic chemistry using the primary literature motivates students to learn deeply and to engage with the important discoveries of the field. Abstract : For many who passed through his classroom, Richard Andersen demonstrated how inorganic chemistry can be taught by incorporating the research literature. The Interactive Online Network of Inorganic Chemists (IONiC) through its website and summer workshops for faculty has supported the development and sharing of more than a hundred exercises or "learning objects" derived from articles highlighting research across the inorganic field. Faculty can adapt and implement these learning objects in their own classrooms to achieve goals such as demonstrating historical context, teaching course material via current research, and elaborating on the scientific process. Literature discussion learning objects highlight current and past research in inorganic chemistry and teach students both chemistry content and how the body of inorganic knowledge is constructed.